2018
DOI: 10.1111/1753-0407.12641
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of automatic bolus calculator with automatic speech recognition in patients with type 1 diabetes: A randomized cross‐over trial

Abstract: The VoiceDiab system improves postprandial glucose control without increasing the time in hyperglycemia or hypoglycemia. Therefore, it may be useful in the treatment of patients with diabetes on intensive insulin therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 23 publications
2
21
0
1
Order By: Relevance
“…One study [13] used the VoiceDiab ® app, which helps users calculate the bolus insulin needed to avoid hypo and hyperglycemia by entering blood glucose data (which can be voice-entered). The app tries to help patients to increase the glycemic time-in-range, within the recommended 70-180 mg/dL.…”
Section: Apps and Mobile Phones For The Control Of Dm1mentioning
confidence: 99%
See 1 more Smart Citation
“…One study [13] used the VoiceDiab ® app, which helps users calculate the bolus insulin needed to avoid hypo and hyperglycemia by entering blood glucose data (which can be voice-entered). The app tries to help patients to increase the glycemic time-in-range, within the recommended 70-180 mg/dL.…”
Section: Apps and Mobile Phones For The Control Of Dm1mentioning
confidence: 99%
“…The app tries to help patients to increase the glycemic time-in-range, within the recommended 70-180 mg/dL. However, after the intervention, no significant changes were found in the HbA1c levels between the control group (6.98) and the intervention group (7.10) [13]. In the study with children and adolescents done by Klee et al, they found that the patients that used the app Webdia (designed for metabolic control in diabetes 1) decreased their level of HbA1c by 0.33 (±0.75), while the HbA1c level increased with the usual care 0.21 (±0.79) [14].…”
Section: Apps and Mobile Phones For The Control Of Dm1mentioning
confidence: 99%
“…According to an analysis of Sussman et al (77), patients with insulin-treated diabetes made errors in more than half of the calculated insulin doses. Several studies reported a clear benefit (79)(80)(81)(82), whereas other authors (83-86) concluded a positive effect only in special aspects. Automated bolus calculators have been available for many years.…”
Section: Automated Bolus Calculatorsmentioning
confidence: 95%
“…How Important Is a Closed-Loop Artificial Pancreas? doi: 10.1111/aor.13338 applications (9). The hybrid CLAP system also needs to be notified that user performs exercises.…”
Section: Invited Editorialmentioning
confidence: 99%
“…Such a procedure is necessary in maintaining a stable glycemia course, but requires additional skills and knowledge from users. Some of them may have problems with such estimations and may use software dietary advisors available as computer or smartphone applications . The hybrid CLAP system also needs to be notified that user performs exercises.…”
mentioning
confidence: 99%